The Long-Term Economic Effects of Polio: Evidence from the Introduction of the Polio Vaccine to Sweden in 1957 - Luis Serratos-Sotelo; Tommy Bengtsson; Anton Nilsson (Institute of Labor Economics (IZA), 2019)
This study explores the impact an exogenous improvement in childhood health has on later-life outcomes. Using extensive and detailed register data from the Swedish Interdisciplinary Panel, we follow individuals exposed to the introduction of the first vaccine against polio in Sweden (birth cohorts 1937-1966) until adulthood in order to quantify the causal effect of polio vaccination on long-term economic outcomes. The results show that, contrary to what has been found in the literature for other health-related interventions, including other vaccines, exposure to the vaccine against polio did not seem to have any long-term effects on the studied adult economic outcomes. Upon closer inspection of how the disease affects children, this might be explained by the fact that no scarring effects from exposure to high incidence of polio were found on adult income, educational achievement, or hospitalizations, which seems to suggest that those who contracted the illness but suffered only the milder symptoms of the disease made a full recovery and had no lifelong sequels as a consequence of the condition. The absence of scarring effects is hypothesized to be related to the pathology and epidemiology of the disease itself, which infects many, but scars only those who suffer the most recognizable paralytic symptoms.
Keywords: I18; 330; vaccine; polio; income; education; early-life; Sweden